Aspectos psicossociais do trabalho e dor musculoesquelética em professores da rede municipal de Salvador-Bahia - Cardoso, Jefferson Paixão (2008)
Over the last year, the modifications that happened in the work field, especially in Education, has been marked by the demands and competences that involves a number of activities in the daily life of school teachers, contributing to the appearance of diseases, including the musculoskeletal complaints. The aim of this study was to describe the predominance of the musculoskeletal pain (DME) according to socio- demographics and occupational factors as well as to examine the association between work-related psychosocial factors and musculoskeletal pain amongst school teachers in Salvador city, Brazil. The study is a cross-sectional, accomplished in 2006, based on an inquiry with teachers of the municipal schools of Salvador. It was applied a standard questionnaire. In order to evaluate the association between psychosocial aspects of work and complaints about pains, it considered the psychosocial aspects of work as independent variable evaluated according to the Model Demand-Control. The dependent variable was composed of musculoskeletal pain, investigated according to its frequency and topography. The co-variable were socio- demographic factors (sex, age, educational level, marital status and number of children) plus job related factors (professional working time, number of teaching classes, number of students, time-table, other teaching job and physical effort). The study made use of logistic regression aiming to accomplish a simultaneous settlement of the studied variables. The undertaken analysis was supported by the SPSS 9.0 and R. Within the applicants, 4.309 reported DME. The prevalence was 23, 7% to lower limbs, 41, 1% to upper limbs and 41, 1% to the back. Women referred to more prevalence for any kind of evaluated pain. Older school teachers, second grade educational level, three or more children and fourteen or more of professional time, also showed more prevalence within the three studied body regions. When analyzing the teaching occupational factors it was observed that teachers with an intense time-table, excessive amount of working hours and with two or more shifts presented more prevalence of DME. The physical effort and environment factors (heat) were associated to the occurrence of DME. The association between work-related psychosocial factors and DME showed that high demanding work and active work were associated to the more prevalence of DME. These results were kept the same even after adjustment for potential disturbing variables. The study enabled to get to know important characteristics of the teaching job, showing negative situations that can reflect on the teachers’ life and teaching quality Therefore, it is necessary the implementation of public politics aiming the improvement of the conditions of teaching work and looking for solutions for reduction, prevention and monitoring of these diseases.